How does total quality management influence the loan quality of the bank? - Banna, Hasanul; Ahmad, Rubi; Koh, Eric Hsieng Yang (Taylor & Francis, 2018)
This paper aims to investigate whether, and to what extent, total quality management (TQM) influences bank loan quality. We propose an approach to measure TQM for evaluating this relationship. The proposed measure is the residual from the Fama–MacBeth regression based on bank efficiency proxied by the income-to-cost ratio. Our proposed TQM measure is statistically significant. We obtain data of 581 US commercial banks from the SNL Financial database for the period 1991–2013 with a total of 13,303 bank-year observations. The result shows that TQM is positively related to bank loan quality. This suggests that the implementation of better TQM can help management to monitor borrowers, improve competition and efficiency, manage good-quality loan portfolios, minimise expenses, and generate more revenues. This research has several implications for regulation, TQM implementation, and policy for the banking industry. In sum, an association between TQM and loan quality allows us to expand our knowledge of the specific role of TQM in bank performance, management decision, and managing loan portfolios.